EVALUASI PENGELOLAAN PERIKANAN CUMI-CUMI SKALA KECIL DENGAN PENDEKATAN EKOSISTEM DI PERAIRAN MEDAN, SUMATERA UTARA - Zairion; Mohammad Mukhlis Kamal; Luky Adrianto; Harahap, Wini Aafini J (Bogor Agricultural University, 2023)
The Medan Sea waters are part of the Indonesian Fisheries Management Area (WPPRI 571) and serve as a fishing ground for squid (Uroteuthis spp.) for small-scale fishers based in Belawan, Medan. Information on the condition of the squid fishery in this area is limited, so a scientific study is needed to determine the status of the fishery as a basis for determining the right management approach. This study aims to assess the current condition of the squid fishery in Belawan using the six domains of indicators in the Ecosystem Approach to Fisheries Management (EAFM): fish resources, habitat, and ecosystem, fishing techniques, economic, social, and institutional. Data were collected through various techniques including direct sampling of squid, in-depth interviews, questionnaires, and secondary data collection. The results showed that the highest value was owned by the fishing technique domain at 280 (good category) and the lowest domain fish resource domain with 168 as a poor category. The low score was due to a decrease in catches and a change in the fishing location. Meanwhile, the aggregate calculation results show that all domains of the Belawan-Medan EAFM are 195 (medium category). This means that some tactical decisions are needed in squid fisheries management in this region. Keywords: EAFM, Medan waters, Small scale fishery, Squid, WPP 571.